1981
DOI: 10.1123/jsp.3.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Demand, Imagery, and Frequency of Mental Rehearsal as Factors Influencing Acquisition of Motor Skills

Abstract: Male college students (N= 39) learned two novel perceptual motor tasks differing in demand across a cognitive-motor continuum, under conditions of physical practice (PP), mental practice (MP), or no practice (NP). On each task, the PP group was given 12 actual trials; the MP group received one actual, nine mental, then two actual trials; and the NP group received one actual trial, 10 minutes rest, then two actual trials. Results showed no difference in learning between MP and NP groups on the predominantly mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 10 publications
6
37
0
2
Order By: Relevance
“…Therefore, the absence of correlation between the QVIM and the participants' performance is more likely due to the fact that this questionnaire is not valid for use with 8-to-10-year-old children. Therefore the results of the present study support those found by several researchers (Corlett et al, 1989;Hall et al, 1992;Ryan & Simons, 1981;Taktek & Rigal, 2005; and suggest that, although it could be administered to a wide range of participants (as underlined by Fournier et al, 1994 andalso Isaac et al, 1986), the QVIM should be adapted for use to the level of children 8-to-10-years of age.…”
Section: The Effects Of Mental Imagery Capacity On the Performance Ofsupporting
confidence: 92%
“…Therefore, the absence of correlation between the QVIM and the participants' performance is more likely due to the fact that this questionnaire is not valid for use with 8-to-10-year-old children. Therefore the results of the present study support those found by several researchers (Corlett et al, 1989;Hall et al, 1992;Ryan & Simons, 1981;Taktek & Rigal, 2005; and suggest that, although it could be administered to a wide range of participants (as underlined by Fournier et al, 1994 andalso Isaac et al, 1986), the QVIM should be adapted for use to the level of children 8-to-10-years of age.…”
Section: The Effects Of Mental Imagery Capacity On the Performance Ofsupporting
confidence: 92%
“…Some researchers (e. g. Sackett, 1934;Ryan & Simons, 1981) suggest that MP is more beneficial for cognitive tasks and has little or no effect on the performance of physical tasks. In line with this suggestion, Schmidt (1982) proposed that MP improves performance during the initial stages of learning and is, therefore, of more use to novices 17 than experts.…”
Section: Movement Imagerymentioning
confidence: 99%
“…It is based, in part, on the assumption that MP is more effective in the early stages of learning and improves the cognitive component of a task more than the motor component (Ryan & Simons, 1981Wrisberg & Ragdale, 1979). The strongest evidence to support this theory has come from studies that have used the bilateral transfer paradigm 18 that is based on the principle that learning exhibits partial transfer from one task to another.…”
Section: 21mentioning
confidence: 99%
“…Mental imagery has proven applications in highperformance athletic training and post-stroke rehabilitation programmes. [5][6][7][8] It has been shown to improve perceptual learning on visual tasks such as spatial discrimination and contrast detection. 9 In surgery, MI as a technique of motor learning and practice has the theoretical advantages of being safe and inexpensive when compared with traditional learning in the operating theatre or in a simulation environment.…”
Section: Introductionmentioning
confidence: 99%